Hard life for sons in the nest? Sex-dependent offspring mortality in Great Tits in urban and forest areas - Nóra Ágh; Henriett Anna Dalvári; Krisztián Szabó; Ivett Pipoly; András Liker (Avian Research)
Sex-biased mortality can occur in birds during development, for example due to sexual differences in energy requirement and/or environmental sensitivity, or the effects of sex hormones or sex differences in the expression of mutations linked to sex chromosomes. The extent of sex-bias in mortality may also be related to environmental conditions that influence offspring development and survival. Urban areas often provide poorer conditions for nestling development resulting in higher offspring mortality compared to natural areas, which may accelerate sex differences in offspring mortality in cities. To test this hypothesis, we examined the sex ratio of dead offspring in Great Tits (Parus major), using 427 samples of unhatched eggs and dead nestlings collected in two urban and two forest sites between 2013 and 2019. The ratio of males in the whole sample of dead offspring (56.9%) was significantly higher than expected by an 1:1 ratio, and the strongest sex biases were detected in urban areas (57.6% males) and in young nestlings (<14 days old, 59.0% males). However, the sex ratios of dead offspring did not differ significantly among study sites and between offspring developmental stages. 29.3% of unhatched eggs contained a visible embryo, and the proportion of embryo-containing unhatched eggs did not differ significantly between urban and forest study sites. These results suggest male-biased offspring mortality in Great Tits, and highlight the need of large datasets to detect subtle differences between habitats and developmental stages.